Integrated Climate Change and Socio-economic Modeling in the Sustainable Management of Water Resources in the Arenal-Tempisque Basin: A Multidisciplinary Approach - Murcia, Carolina (2012)
Current water use in the Tempisque River Basin is unsustainable and will become worse as global and regional climate models forecast a warmer and dryer future. This generates management challenges in both natural and human systems, already strained beyond their limit of economic and biological sustainability. Here, we describe a proposed study to conduct an in depth quantitative analysis of the sustainability of water supply and demand in this basin, and to explore through empirical data and stakeholder input integration and model based scenarios analysis, how climate change may affect ecosystem services through changes in water availability, land use and biodiversity. We think that this approach can provide insights to what actions may be taken, from policy to practice to help maintain or improve water availability and ecosystem services in future years.